Effectiveness of teaching general practitioners skills in brief cognitive behaviour therapy to treat patients with depression: randomised controlled trial. Issue 7343 (20th April 2002) - King, Michael; Davidson, Oliver; Taylor, Fiona; Haines, Andrew; Sharp, Deborah; Turner, Rebecca
Abstract: Objective: To assess the effectiveness of teaching general practitioners skills in brief cognitive behaviour therapy. Design: Parallel group, cluster randomised, controlled trial of an educational package on cognitive behaviour therapy. Setting: General practices in north London. Participants: 84 general practitioner principals and 272 patients attending their practices who scored above the threshold for psychological distress on the hospital anxiety and depression scale. Intervention: A training package of four half days on brief cognitive behaviour therapy. Main outcome measures: Scores on the depression attitude questionnaire (general practitioners) and the Beck depression inventory (patients). Results: Doctors' knowledge of depression and attitudes towards its treatment showed no major difference between intervention and control groups after 6 months. The training had no discernible impact on patients' outcomes. Conclusion: General practitioners may require more training and support than a basic educational package on brief cognitive behaviour therapy to acquire skills to help patients with depression.